We want the funk! [videorecording (DVD)] (PBS Distribution, 2025)
We Want The Funk! is a syncopated voyage through funk's history, from its African and jazz roots to James Brown's early work and the rise of Parliament Funkadelic. Distinctly urban, funk reflected a post- Civil Rights sensibility. The film explores the symbiotic relationship between funk's explosion and the political and racial dynamics of 1970s inner-city America. An unapologetic expression of Black pride, resilience, and joy in the wake of the Civil Rights era. The film explores how funk's infectious grooves became a force of cultural resistance and self-determination. Packed with rare footage, legendary performances, and in-depth interviews with funk pioneers, We Want The Funk! captures the raw energy, deep soul, and unbreakable spirit of funk.